A chromatic confocal probe with a mode-locked femtosecond laser source. (July 2018) - Chen, Xiuguo; Nakamura, Taku; Shimizu, Yuki; Chen, Chong; Chen, Yuan-Liu; Matsukuma, Hiraku; Gao, Wei
Highlights: A chromatic confocal probe was developed using a mode-locked laser source. A new setup was proposed to remove spectral non-smoothness of the laser source. The developed chromatic confocal probe has a depth measurement range of 40 μm. The developed chromatic confocal probe has a depth resolution of better than 30 nm. Abstract: The high spatial coherence and high stability of a mode-locked femtosecond laser source make it ideal for chromatic confocal imaging. Nevertheless, the high non-smoothness of spectrum of the mode-locked laser source often restricts its application in chromatic confocal probes for a wide range of depth measurement. To eliminate the spectral non-smoothness of the mode-locked laser source, we propose a new chromatic confocal setup in such a way that the reflected laser beam is divided into two sub-beams which are then made to pass through two optical paths with different confocal settings where two identical fiber detectors are placed at the focal position and a defocus position, respectively, for acquiring two confocal signals. An axial response is then obtained from the intensity ratio of the two confocal signals for depth measurement. With the proposed confocal setup, we can expand the working spectral range of a mode-locked laser source to its whole spectrum. Theoretical and experimental investigation have revealed that the developed chromatic confocal probe with the specific mode-locked laser source employed in experiments has a measurement sensitivity of about −4 nm/μm, a depth measurement range of about 40 μm, and a depth resolution of better than 30 nm, respectively.